UTILIZATION OF THE GOOGLE FORM APPLICATION AS A MEDIA FOR EVALUATING STUDENT LEARNING AT SMP RAHMAT ISLAMIYAH MEDAN - Hasrian Rudi Setiawan; Mayurida Mayurida (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to describe how the Google Form application is used as a medium in conducting learning evaluation activities at SMP Rahmat Islamiyah Medan. This research is a qualitative descriptive study in class IX students at SMP Rahmat Islamiyah Medan. Data collection was carried out using several data collection techniques, including: interviews, observation and documentation studies. The results show that the Google Form Application has been used by teachers since the emergence of the covid-19 pandemic. The Google Form application is mostly used to evaluate learning for students, both formative evaluation and summative evaluation.